2003
DOI: 10.3310/hta7080
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomised controlled trial assessing the costs and benefits of using structured information and analysis of women's preferences in the management of menorrhagia

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 31 publications
(30 reference statements)
1
33
0
1
Order By: Relevance
“…26 In addition to the PtDA plus decision coaching having lower mean costs, there was a higher number of quality-adjusted life years using the EQ-5D instrument (1.582 v. 1.567) indicating that it was more cost-effective compared with PtDA alone. 30 However, this trial reported no difference in health outcomes between groups using the SF-36. One trial that measured anxiety and depression found no difference in those exposed to coaching plus a PtDA compared with a PtDA alone.…”
Section: Coaching Versus Ptda Alone (Four Trials)mentioning
confidence: 99%
See 1 more Smart Citation
“…26 In addition to the PtDA plus decision coaching having lower mean costs, there was a higher number of quality-adjusted life years using the EQ-5D instrument (1.582 v. 1.567) indicating that it was more cost-effective compared with PtDA alone. 30 However, this trial reported no difference in health outcomes between groups using the SF-36. One trial that measured anxiety and depression found no difference in those exposed to coaching plus a PtDA compared with a PtDA alone.…”
Section: Coaching Versus Ptda Alone (Four Trials)mentioning
confidence: 99%
“…24 This trial reported that couples were more satisfied with coaching but had no difference in knowledge (because similar information was provided to both groups), decisional conflict, uptake of prenatal screening, or pregnancy outcomes. Two other trials compared coaching interventions that included explicit values clarification to PtDA without explicit values clarification and reported the combined intervention was more cost-effective, 26,30 improved values-choice agreement, and decreased decisional conflict. 17 …”
Section: Coaching To Clarify Valuesmentioning
confidence: 99%
“…However, whilst the psychological effects of screening do appear to be minimal, there are burdens associated with diagnosis following screen detection [9,10]. It is possible that information about the type and likelihood of the burdens associated with the screening procedure as well as the possible treatment, when presented alongside the type and likelihood of the benefits, could deter some people from participating in screening programmes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This three-arm randomized trial was described in two separate articles. 14,15 It investigated the use of a PtDA with and without a nurse interview, in women with menorrhagia, compared to usual care. They found that the PtDA plus interview strategy was dominant, by incurring lower costs (d1030) and higher QALYs (1.582) compared to the PtDA alone (d1333, 1.567) or usual care (d1810, 1.574).…”
Section: Resultsmentioning
confidence: 99%